In search of biohappiness : biodiversity and food, health and livehood security - Swaminathan, M. S. [ (Monkombu Sambasivan)] (World Scientific, 2011)
Describes how an era of biohappiness, based on the conservation and sustainable and equitable use of biodiversity, can be launched. This book deals with various aspects of conservation such as in-situ, ex-situ and community conservation. It covers the conservation issues relating to mangroves and other coastal bioresources